Quality of Life in Patients with Central Post-Stroke Pain in Riau, Indonesia: A Cross-Sectional Study - Sukiandra, Riki; Haikal, M. Zacky; Hanania, Dini; Aiko, Novia; Al Rasyid, Daril; Sucipto, Sucipto; Joko, Agus Tri; Juananda, Desby; Maryanti, Yossi; Adlii, Muhammad Faa’iz (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2026)
Background: Central Post-Stroke Pain (CPSP) is a chronic neuropathic complication of stroke that substantially impairs long-term well-being. While its clinical characteristics are increasingly recognized, data regarding the multidimensional quality of life (QoL) impact of CPSP in regional Indonesian populations remain limited. This study aimed to describe the QoL profile of CPSP patients at Arifin Achmad General Hospital to provide a comprehensive understanding of the disease burden. Methods: A descriptive cross-sectional study was conducted from August to October 2025 at the Neurology Outpatient Clinic of Arifin Achmad General Hospital, Riau. Forty-four patients diagnosed with CPSP were included. QoL was assessed using the validated Indonesian version of the Stroke-Specific Quality of Life (SS-QoL) scale. Descriptive univariate analysis was performed to determine median scores across domains. Results: QoL scores demonstrated marked heterogeneity across domains. The Vision domain showed the highest median score (4.0), whereas Social Role recorded the lowest (2.7). Notable reductions were observed in Work, Upper Extremity Function, and Energy domains. In contrast, Language and Self-care domains were relatively preserved. These findings indicate that although basic functional abilities may remain intact, CPSP significantly compromises social participation, occupational capacity, and physical activity. Conclusion: CPSP imposes a substantial multidimensional burden, particularly affecting social engagement, productivity, and physical endurance. Comprehensive management strategies extending beyond pharmacological pain control are essential to address the psychosocial and functional consequences of CPSP. Further longitudinal studies with larger sample sizes are needed to clarify determinants of QoL outcomes in this population.